Retrospective and concurrent perspectives of the transition into senior professional female football within the United Kingdom. (March 2021) - McGreary, Michael; Morris, Robert; Eubank, Martin
Abstract: In the United Kingdom (UK), professional female football has grown exponentially in recent years, including with the advent of the Women's Super League. Given this growth, the present study aimed to (a) to explore the junior-to-senior transition in the UK female football players (i.e., perceived demands, barriers, resources, and coping strategies); (b) to analyze how changes in the UK female football context (i.e., increased professionalization) influenced players' perception of the transition. Six professional female soccer players from two groups took part in the study; senior athlete (N = 3) and transitional athletes (N = 3). To acquire a holistic understanding, semi-structured interviews were conducted with all athletes. Results highlighted transitional athletes appeared to have a different JST experience compared to the senior group, with the difference in experience attributed to the increased professionalization of female football. In particular, demands associated with being a dual career athlete and greater difficulty balancing the competing demands. As a result, transitional athletes also engaged in more coping strategies. This study provides valuable findings in relation to the JST in professional female football and the context of the increasing professionalization of female football in the UK. Highlights: Retrospective and concurrent experiences of JST in UK professional female soccer. Dual-career represented salient demands and challenges for athletes. Transitional athletes JST experience differed slightly to senior athletes. Key differences attributed to increased professionalization of female soccer in UK.